Ethics of information in the digital AGE - Paletta, Francisco Carlos; Silva, Armando Manuel Barreiros da (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2017)
This study aims to present partial results on the research Project Tecnologia da Informação em Biblioteca Digital e Sistemas Abertos – Estudos de Usuário da Informação na Web de Dados (Information Technology in Digital Library and Open Systems – Studies on Users of Information on Data Web), conducted by the School of Communications and Arts from University of São Paulo in cooperation with the Faculty of Letters of the University of Porto. The study presents reflections on ethical dimensions that accompany the current digital era. It discusses the importance of understanding the demands of the information user in the Data Web, with a view to teach a course named Ethics of Information at undergraduate programs in Librarianship, Archivology, Museology, and Information Science, which condenses these reflections and problems, Developing skills for an ethical action in the formation of the information professional in the network society. Palavras-chave: Ethics. Ethics of Information. Digital age. Information Science. Scientific Cooperation. Pedagogical Experience. Link: http://www.ies.ufpb.br/ojs2/index.php/ies/article/view/32983